Foreword - David Porter (Journal of Innovation in Polytechnic Education)
Micro-credentials and their use are hot topics in higher education in 2021. As the World Economic Forum Jobs 2020 report (World Economic Forum, 2020) noted, there is an increasing need to provide short-timeframe opportunities for reskilling and upskilling that will not diminish as we move forward. Driven by this need to reskill or upskill learners, institutions are looking closely at new practice models that will allow them to offer training and certification in smaller units of learning directly tied to workplace needs. This opportunity to create customizable learning experiences for individuals has catalysed a movement to harness ideas originally designed for open badging (OpenBadges.org, 2020) with the developing requirement for institutions to offer digital credentials for all learners (AACRAO, 2020). The resulting fusion has led to the exploration and development of micro-credentials, inspired by the collective value proposition for learners, higher education institutions and employers.